2019
DOI: 10.1523/jneurosci.2771-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

The MAP1B Binding Domain of Nav1.6 Is Required for Stable Expression at the Axon Initial Segment

Abstract: Na v 1.6 (SCN8A) is a major voltage-gated sodium channel in the mammalian CNS, and is highly concentrated at the axon initial segment (AIS). As previously demonstrated, the microtubule associated protein MAP1B binds the cytoplasmic N terminus of Na v 1.6, and this interaction is disrupted by the mutation p.VAVP(77-80)AAAA. We now demonstrate that this mutation results in WT expression levels on the somatic surface but reduced surface expression at the AIS of cultured rat embryonic hippocampal neurons from both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 64 publications
0
35
0
Order By: Relevance
“…It was reasonable to assume that MAP1B binding was involved in the forward trafficking of Na v 1.6 since, in addition to its classical role in microtubule stabilization, MAP1B is also known to regulate the localization, function and trafficking of different channels and receptors [96]. However, as our recent work demonstrated, and to our surprise, the Na v 1.6 MAPM traffics to the somatic surface of hippocampal neurons but is not concentrated within the AIS (Figure 4(a)) [28]. While we expected that this distribution was due to a lack of trafficking to the AIS, the fluorescent biotinylation assay described above confirmed that this was not the case, with the MAPM being readily delivered to the AIS surface where it was immediately immobilized just like the wild-type channel.…”
Section: Trafficking Mechanismsmentioning
confidence: 61%
See 3 more Smart Citations
“…It was reasonable to assume that MAP1B binding was involved in the forward trafficking of Na v 1.6 since, in addition to its classical role in microtubule stabilization, MAP1B is also known to regulate the localization, function and trafficking of different channels and receptors [96]. However, as our recent work demonstrated, and to our surprise, the Na v 1.6 MAPM traffics to the somatic surface of hippocampal neurons but is not concentrated within the AIS (Figure 4(a)) [28]. While we expected that this distribution was due to a lack of trafficking to the AIS, the fluorescent biotinylation assay described above confirmed that this was not the case, with the MAPM being readily delivered to the AIS surface where it was immediately immobilized just like the wild-type channel.…”
Section: Trafficking Mechanismsmentioning
confidence: 61%
“…While we expected that this distribution was due to a lack of trafficking to the AIS, the fluorescent biotinylation assay described above confirmed that this was not the case, with the MAPM being readily delivered to the AIS surface where it was immediately immobilized just like the wild-type channel. We found that MAPM is not concentrated at the AIS because, without MAP1B binding, it is internalized via compartment-specific Na v 1.6 endocytosis [28]. Although MAPM channels are still tethered at the AIS plasma membrane by AnkG binding (as demonstrated by their restricted diffusion, similar to wild-type Na v 1.6 channels), these channels are endocytosed from the axonal compartment when MAP1B is not able to bind to Na v 1.6 (as illustrated in Figure 4(b)).…”
Section: Trafficking Mechanismsmentioning
confidence: 81%
See 2 more Smart Citations
“…Therefore, ARF4 ϩ/Ϫ /ARF5 Ϫ/Ϫ mouse PCs may display a failure in trafficking Nav1.6 proteins to the AIS via an ankyrin-G-independent mechanism. However, it is also possible that the decreased localization of Nav1.6 to the AIS depends on the enhanced Nav1.6 endocytosis from the AIS, rather than a reduced forward trafficking to the AIS (Solé et al, 2019). The trafficking of Nav1.6 proteins to the AIS needs to be examined directly in real-time imaging to determine whether the maintenance of Nav1.6 proteins in the AIS is affected.…”
Section: Function Of Class II Arfsmentioning
confidence: 99%